PERTANGGUNGJAWABAN PEJABAT NEGARA YANG MELAKUKAN PENYALAHGUNAAN KEWENANGAN (MENURUT PERSPEKTIF HUKUM ADMINISTRASI NEGARA) - Yudistira, Yudistira (UNES Law Review, 2023)
Accountability for the actions of the government arises from the existence of 2 things, namely the existence of authority and the existence of rights and obligations. The authority of these rights and obligations is an act of the government that must be accounted for. Government accountability is in the form of legal accountability (criminal, civil and state administration) There are 3 types of accountability for state officials morally, namely : Hierarchical responsibility, responsibility for a political product is borne by the person with the highest position in the chain of formal and informal authority. Collective Responsibility, based on the premise that many political products are the result of the actions of many different people, so that individual contributions may not be identified at all and certainly cannot really be distinguished from the contributions of others. An official is morally responsible for a policy product only if (1) the official's actions or omissions are the cause of the policy product; and (2) these acts or omissions were not committed in ignorance or under duress. Furthermore, legal responsibility under the Act. No. 30 of 2014 concerning Government Administration of Government Internal Supervisory Apparatuses (APIP) and the State Administrative Court conduct an examination if the policy carried out is found to be in the form of losses. Efforts that can be made to prevent abuse of authority by state officials Preventive or prevention efforts can be carried out by means of: Anti-corruption education, Anti-corruption campaigns, one topic. Socialization on the eradication of criminal acts of corruption, organized through education and training activities, seminars, workshops, discussions, upgrading, lectures and religious sermons with the aim of creating public awareness and legal compliance in order to participate in assisting state administrators Research, study and development of eradicating corruption crimes.